Influence of aspect ratio of tunnel on smoke temperature distribution under ceiling in near field of fire source. (5th August 2016) - Ji, Jie; Bi, Yubo; Venkatasubbaiah, Kondapalli; Li, Kaiyuan
Highlights: Experiments were conducted using a model tunnel with adjustable width. The effect of tunnel width on mass loss rate is studied. Correlations for predicting the ceiling temperature distributions are proposed. The proposed correlations are compared with literature and show a good agreement. Abstract: Former studies usually used model tunnels with fixed width while in reality the tunnel width can be different between different tunnels. In the current study, a set of small scale experiments were conducted using a model tunnel with adjustable width. The influences of tunnel width on mass loss rate, maximum smoke temperature and temperature distributions under the ceiling were investigated. Results show that under the current experimental conditions, the tunnel width has little influence on the mass loss rate and maximum smoke temperature under the ceiling. However, tunnel width significantly affects the smoke temperature distribution. The smoke temperature under the ceiling decays more slowly at both longitudinal and transverse directions as tunnel width decreases. Empirical models are developed for both longitudinal and transverse temperature distributions which take into account the effects of tunnel width and dimensionless heat release rate. The models include exponential type functions. The index of the exponential function is proportional to the dimensionless heat release rate to the power of n . The value of n is 0.4 for longitudinal distribution and 0.5 for transverse distribution.